MALARIA AND HIV IN ADULTS: When The Parasite runs into The Virus - Emanuele Focà; Silvia Odolini; Nigritella Brianese; Gianpiero Carosi (Mediterranean Journal of Hematology and Infectious Diseases)
Malaria and HIV/AIDS are among the principal causes of morbidity and mortality worldwide, particularly in resource-limited settings such as sub-Saharan Africa. Despite the international community’s efforts to reduce incidence and prevalence of these diseases, they remain a global public health problem. Clinical manifestations of malaria may be more severe in HIV infected patients, which have higher risks of severe malaria and malaria related death. Co-infected pregnant women, children and international travelers from non-malaria endemic countries are at higher risk of clinical complications. However, there is a paucity and conflicting data regarding malaria and HIV co-infection, particularly on how HIV infection can modify the response to antimalarial drugs and about drug-interactions between antiretroviral agents and artemisinin-based combined regimens. Moreover, consulting HIV-infected international travelers and physicians specialized in HIV care and travel medicine should prescribe an adequate chemoprophylaxis in patients travelling towards malaria endemic areas and pay attention on interactions between antiretrovirals and antimalarial prophylaxis drugs in order to prevent clinical complications of this co-infection.